Contrato de trabalho intermitente direito do trabalho - Alves, Flavia da Silva (2018)
The subject is of significant relevance to labor law due to the recent reform of the consolidation of labor laws and the controversy that arises from different interpretations about the current legislation. This study aims to analyze the main aspects of intermittent employment, as well as to list several situations that have not been debated yet, given that the legislation is absent, as well as to examine the constitutional and formal aspects in the enforcement of labor laws in face of divergences arising from the labor law reform, regarding the use of the intermittent employment contract. The objective is to examine the conceptual aspects of the employment contract, addressing the subject from its original concept, also presenting a brief comparative study of the intermittent employment contract, the advantages and disadvantages of this modality of employment, the discussion regarding its validity before the constitutional actions that discuss the subject, as well as its reflexes in the society and in social security. The present study was developed based on the dialectical, deductive and partially inductive bibliographic methods, using as sources the constitutional and infraconstitutional legislation, opinion of jurists, norms of international law and court precedents